Pendidikan Islam sebagai Pilar Moderasi Beragama di Indonesia - Tito Erliando Saputra; Alvin Ardiansyah Putra; Gusmaneli Gusmaneli (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Indonesia is a country with a lot of diversity, both in terms of culture, natural resources and religion. In Indonesia, there are 6 official religions, namely Islam, Catholic Christianity, Protestant Christianity, Hinduism, Buddhism and Confucianism. Therefore, inter-religious conflicts are prone to occur in Indonesia. Religious moderation is the key to maintaining social harmony and preventing radicalization and intolerance. This study discusses how Islamic education, through the curriculum, teaching methods and values ​​taught, can contribute to instilling an inclusive, tolerant attitude and respect for differences. Through literature review and concept analysis, this article emphasizes that Islamic education, both formal and non-formal, can be the main pillar in strengthening religious moderation in Indonesia.